Effect of cervical insemination with frozen semen on fertility of Indian goat breed - RANJAN, R; GOEL, A K; KHARCHE, S D; PRIYADHARSINI, R; RAMACHANDRAN, N; SINGH, M K; KUMAR, R; DIGE, M S; BHUSHAN, S; CHOUDHARY, U B; KUMAR, S; JINDAL, S K; et al. (The Indian Journal of Animal Sciences, 2020)
Artificial Insemination (AI) has great potential to multiply superior quality of goat with faster rate in spite of lower conception rate. This technique will spread elite genetic material throughout a population and is also important for breed conservation and has paved the way for other reproductive biotechnologies. Ejaculates from bucks aged between 2–4 years old from Jamunapari, Barbari, Sirohi and Jakhrana were collected using artificial vagina, twice a week. Immediately after collection, the volume, colour, consistency, and mass motility of ejaculate were assessed and were extended with Tris -Egg yolk- Fructose diluent having 10% (v/v) egg yolk and glycerol 6% (v/v). Sperm concentrations were adjusted to 1×108/ml and diluted semen was equilibrated at 5°C for 4 h before being frozen. The post thaw motility in Jamunapari and Barbari was significantly higher then Jakhrana and Sirohi. In two major breeding seasons (May–June and October–November), 181 goats of different breeds (Barbari, Jakhrana, Jamunapari and Sirohi) including 35 goats in villages were intra-cervical inseminated with frozen semen in natural estrous condition. The kidding percentage in Barbari, Jamunapari, Jakhrana and Sirohi were 53.12±2.40%, 34.61±1.96%, 26.53±2.12% and 28.57±2.32% respectively. Overall, a success rate of 37.57% was recorded on the basis of actual kidding rate irrespective of goat breed maintained at this institute under semi-intensive management system. The best post thaw quality of buck semen and comparative deeper cervical insemination in Barbari and Jamunapri breeds results in higher conception and kidding percent compared to other breeds (Sirohi and Jakhrana).